Material transfer agreements in genetic resources exchange: The case of the International Agricultural Research Centres - Barton, John H.; Siebeck, Wolfgang E.; International Plant Genetic Resources Institute (1994)
The Convention on Biological Diversity, which provides incentives for countries to exercise sovereign rights over genetic resources in their territories, has led several countries to develop policies and strategies governing the conservation and use of genetic diversity, including conditions for its release. A system is required to facilitate the unhindered movement of genetic resources and the fair and equitable sharing of benefits derived from their use. This publication, a contribution to the debate on these issues, suggests mechanisms by which these objectives might be achieved.